Analisis Nilai Tambah Produk Olahan Jahe Merah di Provinsi Kalimantan Timur (Studi Kasus Pengolahan Jahe Merah Instan pada Kelompok Wanita Tani Lestari Kelurahan Lempake Kacamatan Samarinda Utara) - Eka Nor Santi; Erwan Wahyudi (Jurnal Agribis, 2021)
This research was conducted to determine the added value of agricultural products, especially in the processing of red ginger. The research method used is descriptive research, with the research location in the Sustainable on Kelompok Wanita Tani (KWT), Lempake sub-distric, North Samarinda distric. The research method used is descriptive research and the analysis used to calculate the added value is the Hayami method. The results showed that the red ginger processing business was profitable and had added value. The amount of red ginger used is 50 kg / month and the income is IDR 7.013.044 per month. Meanwhile, the added value, which is the difference between the output value and the contribution of other inputs and the price of raw materials, namely Red Ginger, which is processed into Instant Red Ginger, is IDR Rp 185.261/ kg.